RARE-13. CHARACTERIZATION OF ADULT MEDULLOBLASTOMA PATIENTS AT RECURRENCE: RETROSPECTIVE REVIEW OF THE MD ANDERSON CANCER CENTER EXPERIENCE. (5th November 2018) - Mastall, Maximilian; Majd, Nazanin; Fuller, Gregory; Gule-Monroe, Maria; T Huse, Jason; Khatua, Soumen; Rao, Ganesh; Sandberg, David; Wefel, Jeffrey; Yeboa, Debra; Zaky, Wafik; Mahajan, Anita; et al.
Abstract: BACKGROUND: Adult medulloblastoma (MB) is rare, accounting for 150–300 new cases in the US annually. Given the low incidence, prospective studies are challenging, and treatment guidelines and recurrence characteristic are derived from pediatrics. However, adult MB is a distinct entity, and further studies are warranted. Surgery followed by radiation and chemotherapy are accepted treatment modalities, but there is limited information on characteristics and outcomes of adult MB at recurrence. METHODS: 136 adult MB patients (≥18 years at diagnosis) were identified at MD Anderson from January 1978 to April 2017. Median progression-free survival (PFS) and overall survival (mOS) were estimated using the Kaplan-Meier method. RESULTS: Median age 28 (18–63); 53.7% standard risk (SR) (minimal residual disease and no metastasis) and 32.4% high risk (HR) (indeterminate in 19). Median PFS and mOS for the entire cohort were 98 and 133 months, respectively. No residual tumor after initial surgery and use of adjuvant chemotherapy were associated with improved survival, but M status was not. 44.9% had developed recurrence at median follow-up of 59.5 months (34.4% were SR and 42.6% were HR); median time to 1 st recurrence was 34 months; mOS after first recurrence was 23 months. Local recurrence was associated with improved survival compared to distant recurrence. CONCLUSION: To our knowledge, this is the largest series of adult MB from a single institution. Extent of surgery was associated with improved survival, which is an established positive prognostic indicator in pediatric MB but has been controversial in adults. Adjuvant chemotherapy was associated with improved survival in patients without residual tumor after first surgery. Late recurrences were more common than in the pediatric population, highlighting the need for long term follow-up. Adult MB patients have a poor mOS of 23 months after recurrence, and optimizing treatments at recurrence is an unmet need.